Pengaruh Kedisiplinan, Tingkat Pendidikan Dan Pengalaman Kerja Terhadap Kinerja Karyawan PT. ISS Indonesia Di Gresik (GEMA EKONOMI, 2019)
Thisstudy aimed to analyze the effectof Discipline, level of education, andÃƒÆ’Ã†â€™ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â  work experience effect on theemployees performanceinPT.ISS IndonesiainGresik. The data were obtainedÃƒÆ’Ã†â€™ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â  from the presentation of data from the respondents (questionnaire). And results of other studies that relefan with the object studied, in this case the primary data from the PT. ISS Indonessia in Gresik. The statistical analysis used in this study is multiple regression analysis using SPSS 16. The findings of the study suggest that the Discipline, evel of education, and work experienceÃƒÆ’Ã†â€™ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â  simultaneously (together) and significantly efect on the employees performance in PT. ISS Indonesia in Gresik. This is evidenced by the results of the F test with a significance level below 0,05. Discipline, level of education, and work experienceÃƒÆ’Ã†â€™ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â  variable are partially an significantly effect on the employees performance. This is evidenced by the result of the t test, independent variables are effect each dependent variable if the significance level below 0,05. ÃƒÆ’Ã†â€™ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â Keywords : Discpline, level of education, work experience and employees perfomance.DOI : 10.5281/zenodo.3474545